Preservation of Cowpea (Vigna unguiculata (L.) Walp) Grains against Cowpea Bruchids (Callosobruchus maculatus) Using Neem and Moringa Seed Oils - Joana O. Ilesanmi; Daniel T. Gungula (International Journal of Agronomy)
This study was conducted to determine the effects of neem (Azadirachta indica A. Juss) and moringa (Moringa oleifera) seed oils on the storability of cowpea grain. Cowpea samples were treated with various concentrations (0.5, 1.0, and 1.5 mL/200 g cowpea) of pure neem and moringa oils and their mixtures in ratios of 1:1, 1:2, and 1:3. The treated cowpea samples were stored for 180 days. Data were collected every 30 days on number of eggs laid, total weevil population, and percentage of uninfested grains and analysed statistically. Significantly different means were compared using LSD at 𝑃<.05. Increasing oil concentration resulted in better cowpea protection, for example, in oviposition where the control had 6513 eggs, only 8 eggs were recorded in pure neem oil-treated sample at 0.5 mL/200 g. Generally, better results were obtained with higher oil concentrations either in their pure forms or mixtures. The control had a total weevil population of 4988, while most treated samples had none. The control samples had 0% uninfested grains, while 73–94% of uninfested grains were observed in treated samples after 6 months of storage. Therefore, mixture of the oils at 1.5 mL/200 g can be effectively used to store cowpea.